Vitamin C-Induced Oxalate Nephropathy - Jorge Lamarche; Reji Nair; Alfredo Peguero; Craig Courville (International Journal of Nephrology)
Although a multitude of syndromes have been thoroughly described as a result of vitamin deficiencies, over consumption of such substances may also be quite dangerous. Intratubular crystallization of calcium oxalate as a result of hyperoxaluria can cause acute renal failure. This type of renal failure is known as oxalate nephropathy. Hyperoxaluria occurs as a result of inherited enzymatic deficiencies known as primary hyperoxaluria or from exogenous sources known as secondary hyperoxaluria. Extensive literature has reported and explained the mechanism of increased absorption of oxalate in malabsorptive syndromes leading to renal injury. However, other causes of secondary hyperoxaluria may also take place either via direct dietary consumption of oxalate rich products or via other substances which may metabolize into oxalate within the body. Vitamin C is metabolized to oxalate. Oral or parenteral administration of this vitamin has been used in multiple settings such as an alternative treatment of malignancy or as an immune booster. This article presents a clinical case in which ingestion of high amounts of vitamin C lead to oxalate nephropathy. This article further reviews other previously published cases in order to illustrate and highlight the potential renal harm this vitamin poses if consumed in excessive amounts.